2019
DOI: 10.1111/pan.13662
|View full text |Cite
|
Sign up to set email alerts
|

The development of an opioid sparing anesthesia protocol for pediatric ambulatory tonsillectomy and adenotonsillectomy surgery—A quality improvement project

Abstract: Pain management following pediatric tonsillectomy and adenotonsillectomy surgery is challenging and traditionally involves perioperative opioids. However, the recent national opioid shortage compelled anesthesiologists at Bellevue Surgery Center to identify an alternative perioperative analgesic regimen that minimizes opioids yet provides effective pain relief. We assembled an interdisciplinary quality improvement team to trial a series of analgesic protocols using the Plan-Do-Study-Act cycle.Initially, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 31 publications
3
57
0
Order By: Relevance
“…in pediatric patients through the use of regional anesthesia and non-opioid medications for various surgical procedures. 8,11,12 Our pilot study utilized an opioid-sparing technique for intraoperative and postoperative analgesia that included 4 medications dextromethorphan, acetaminophen, dexmedetomidine, and ketamine. At our institution, preoperative acetaminophen and intraoperative dexmedetomidine are frequently administered, but the use of the other two medications (dextromethorphan and ketamine) was unique additions to the perioperative regimen.…”
Section: Dovepressmentioning
confidence: 99%
See 2 more Smart Citations
“…in pediatric patients through the use of regional anesthesia and non-opioid medications for various surgical procedures. 8,11,12 Our pilot study utilized an opioid-sparing technique for intraoperative and postoperative analgesia that included 4 medications dextromethorphan, acetaminophen, dexmedetomidine, and ketamine. At our institution, preoperative acetaminophen and intraoperative dexmedetomidine are frequently administered, but the use of the other two medications (dextromethorphan and ketamine) was unique additions to the perioperative regimen.…”
Section: Dovepressmentioning
confidence: 99%
“…To our knowledge, this is the first study describing the combined use of dextromethorphan, acetaminophen, ketamine and dexmedetomidine to manage pain for pediatric patients undergoing otolaryngologic procedures. Although the use of ketorolac has been utilized for pediatric otolaryngological procedures without a reported increase of postoperative bleeding, 11,38,39 a lack of consensus remains due to institutionally dependent tonsillar bleeding rates and differing perceptions among otolaryngologists regarding risk factors and causes of post tonsillectomy hemorrhage. Of note, the pediatric otolaryngologists within our institution preferred to exclude ketorolac in the current study due to conflicting evidence regarding the potential risk of bleeding.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…A rapidly growing body of research has demonstrated multiple strategies for reducing postoperative opioid prescriptions, including reducing pill counts, inclusion of nonopioid alternatives, focused patient and provider education as well as preoperative medication regimes. 17‐24 However, within academic medical centers, the nearly 135,000 residents training across all specialties frequently serve as the primary prescribers of postoperative pain control regimens 3,15,25,26 . Resident physicians rarely receive formal training in opioid prescription management and most report low levels of comfort with prescribing these medications 3 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Other subsequent commentaries and studies have confirmed the challenges associated with treating inpatients' pain due to the APQ reductions, [12][13][14][15][16][17][18] including those addressing treating children perioperatively and postoperatively. 19,20 Up to this point, reports of APQ reduction-related shortages of oral opioids are only anecdotal, with numerous reports from patients on social media. In these cases, the patients (generally suffering from chronic non-cancer pain) report that their pharmacies have "run out" of medications that they have taken for many years, although these patients have not been privy to whether these lacks of availability are due to APQ reductions or other supplyside issues within their own pharmacies.…”
mentioning
confidence: 99%